The effect of fear of missing out and sales promotion on virtual goods impulse buying: The mediating role of positive emotion among Roblox users - Helga Tabina Putri Alifah; Bukar Isa Gamawa (PT Bina Perfidia Akademia, 2026)
The rapid growth of virtual goods transactions on digital gaming platforms has increased impulsive buying behavior, yet the mediating role of positive emotion in the relationship between Fear of Missing Out (FOMO), sales promotion, and impulsive buying remains underexplored. This study aims to examine the direct effects of FOMO and sales promotion on Robux impulsive buying among Roblox users and to investigate the mediating role of positive emotion. A quantitative approach was employed using data from 251 Roblox users who had purchased Robux, which were analyzed through path analysis and the Sobel Test. The findings reveal that FOMO, sales promotion, and positive emotion have positive and significant effects on impulsive buying, while positive emotion significantly mediates the effects of FOMO and sales promotion on impulsive buying. This study contributes to the digital consumer behavior literature by demonstrating that positive emotion serves as the psychological mechanism linking social and marketing stimuli to impulsive buying in virtual goods consumption. Abstrak Perkembangan transaksi virtual goods pada platform permainan digital meningkatkan kecenderungan impulsive buying, namun mekanisme yang menjelaskan peran positive emotion dalam memediasi pengaruh Fear of Missing Out (FOMO) dan sales promotion masih belum banyak dikaji. Penelitian ini bertujuan menganalisis pengaruh langsung FOMO dan sales promotion terhadap impulsive buying Robux pada pengguna Roblox serta menguji peran mediasi positive emotion. Penelitian menggunakan pendekatan kuantitatif dengan melibatkan 251 pengguna Roblox yang pernah membeli Robux, kemudian dianalisis menggunakan path analysis dan Sobel Test. Hasil penelitian menunjukkan bahwa FOMO, sales promotion, dan positive emotion berpengaruh positif dan signifikan terhadap impulsive buying, sedangkan positive emotion terbukti memediasi pengaruh FOMO dan sales promotion terhadap impulsive buying. Penelitian ini berkontribusi pada pengembangan kajian perilaku konsumen digital dengan menegaskan positive emotion sebagai mekanisme psikologis yang menghubungkan stimulus sosial dan pemasaran dalam pembentukan perilaku pembelian impulsif pada virtual goods.